Error Estimates for the Averaging Method for Pulse Oscillation Systems - Lakusta, L. M.; Petryshyn, R. I.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We prove new theorems on the justification of the averaging method on a segment and semiaxis in multifrequency oscillation systems with pulse action at fixed times.